A new stygobitic species of Stygocarididae (Crustacea: Anaspidacea) from South America - Peralta, Marcela (Zootaxa, 2014)
The only South American Anaspidacean families are the Stygocarididae Noodt and the monotipic Patagonaspididae Grosso & Peralta. I describe a new Stygocarididae, Parastygocaris luisgrossoi n. sp. from the hyporheic zone of a stream in Sierra de San Luis, Argentina. The main characters of the new species include: antennula outer flagellum with 9–10 articles, sexual dimorphism in flagella; antenna with 4-segmented peduncle and 5-articulate flagellum; maxilla with row of 8 setae along inner margin of proximal endite; uropod: inner margin of protopod with 7–8 setae and distal segment of exopod lined by 7 setae; pereopod 6 female with 1 long plumose seta on basis. The morphology and chaetotaxy of the new taxon is compared with congeneric species. The long evolutionary history of the Gondwanan Anaspidacea and the accompanying fauna of the new species, suggest the probable existence of an ancient groundwater basin in western Argentina, south of 28ºS that would have harboured interstitial fauna of great and diverse antiquity.